Design of a Microcontroller-Based Corn Dryer - Wiwik Wiharti; Zulka Hendri; Yona Mayura; Ihsan Lumasa Rimra; Ikhwan Razikin (Brilliance: Research of Artificial Intelligence, 2023)
Maize drying is a crucial procedure in the agricultural and food industries, aimed at decreasing the moisture content of maize kernels to prolong their shelf life, inhibit microbial growth and maintain their quality. Two common methods for drying corn include natural techniques, which involve drying the maize in the sun, and artificial techniques, where specialized equipment such as hot air dryers, drum dryers and microwaves are employed. The author constructed a corn dryer utilizing Arduino. This device employs heat elements and fans to expedite the corn drying process. The tool can significantly quicken the corn drying process. The author utilises a DHT22 sensor to gauge temperature and humidity levels of the corn. The device is capable of generating temperatures ranging from 20?C to 90?C, thanks to the assistance of the DHT22 sensor during the drying process.